2017
DOI: 10.1002/ajpa.23361
|View full text |Cite
|
Sign up to set email alerts
|

Proximate cause, anatomical correlates, and obstetrical implication of a supernumerary lumbar vertebra in humans

Abstract: Sexual difference in number of PSV may be due to tempo of somite formation and Hox gene activation. Hypothesis is not supported that a supernumerary lumbar vertebra is due to inactivation of Hoxd-11. The presence of a supernumerary lumbar vertebra is associated with small pelvic inlet circumference, which can be obstetrically disadvantageous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 95 publications
(125 reference statements)
1
2
0
Order By: Relevance
“…In those specimens, the first coccygeal element is incorporated within the sacrum by complete fusion. In our sample, sacralizations of the coccyx were relatively common (32%) and frequently occurred in conjunction with lumbarizations, which is in accordance with previous findings (Derry, 1912 ; Mitchell, 1936 ; Tague, 2018 ). Therefore, attention must be paid not only to the first but also to the last sacral element, specifically the interarticular cornua, since such situations are otherwise not recognizable in isolated sacra.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In those specimens, the first coccygeal element is incorporated within the sacrum by complete fusion. In our sample, sacralizations of the coccyx were relatively common (32%) and frequently occurred in conjunction with lumbarizations, which is in accordance with previous findings (Derry, 1912 ; Mitchell, 1936 ; Tague, 2018 ). Therefore, attention must be paid not only to the first but also to the last sacral element, specifically the interarticular cornua, since such situations are otherwise not recognizable in isolated sacra.…”
Section: Discussionsupporting
confidence: 93%
“…Many authors suggested that obstetric disadvantages might result from segmentation anomalies (Breus & Kolisko, 1904;Buttenberg, 1962;Diehl & Holmberg, 1968;Kirchhoff, 1949;Kirchhoff, 1958;Mahato, 2018;Müller, 1932;Nastoulis et al, 2019;Tague, 2018;Winter, 1953). The pelvic inlet dimensions, for example, the conjugate, the inlet circumference, and the transverse diameter, may therefore vary with changes in the relative position of the promontory, sacral breadth, height, and sagittal curvature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation